2023
DOI: 10.1021/acsami.2c22803
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Regulation Engineering in the Carbon Nitride Nanoflower for Strong and Stable Electrochemiluminescence

Abstract: Cathode electrochemiluminescence (ECL) of C 3 N 4 material has suffered from weak and unstable ECL emission for a long time, which greatly limits its practical application. Herein, a novel approach was developed to improve the ECL performance by regulating the crystallinity of the C 3 N 4 nanoflower for the first time. The high-crystalline C 3 N 4 nanoflower achieved a pretty strong ECL signal as well as excellent long-term stability compared to low-crystalline C 3 N 4 when K 2 S 2 O 8 was used as a co-reactan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…It was seen that the maximum emission appeared around 470 nm (Figure b), which is consistent with the ECL emission spectra of the sole CN-modified electrode (Figure S4, Supporting Information). Therefore, the ECL luminophor should be the excited-state CN. The ECL signals of three repeats of all cases under −1.5–0 V potential were shown in Figure c. The similar ECL intensities of the three repeats indicate the high stability of the ECL probe.…”
Section: Resultsmentioning
confidence: 85%
“…It was seen that the maximum emission appeared around 470 nm (Figure b), which is consistent with the ECL emission spectra of the sole CN-modified electrode (Figure S4, Supporting Information). Therefore, the ECL luminophor should be the excited-state CN. The ECL signals of three repeats of all cases under −1.5–0 V potential were shown in Figure c. The similar ECL intensities of the three repeats indicate the high stability of the ECL probe.…”
Section: Resultsmentioning
confidence: 85%
“…The unique luminescence mechanism enables ECL technology to exhibit high sensitivity and near-zero background signal, thus being extensively applied in the biosensing field. ECL luminophore is an essential player in the construction of ECL biosensors. Among the various ECL luminophores that have been developed, graphitic carbon nitride (g-C 3 N 4 ) has aroused considerable attention because of its low toxicity, good biocompatibility, and adjustable luminescence characteristics. Since Cheng et al first reported the ECL property of g-C 3 N 4 , various g-C 3 N 4 -based nanocomposites and vacancy-modified g-C 3 N 4 have sprung up and been successfully used to construct ECL sensors. These g-C 3 N 4 -based ECL sensing platforms mainly relied on their cathode ECL emission with peroxydisulfate (S 2 O 8 2– ) as coreactant. As the strong background interference of S 2 O 8 2– cannot be ignored, dissolved oxygen (O 2 ) and H 2 O 2 have been considered as alternative coreactants for enhancing cathodic ECL of g-C 3 N 4 .…”
Section: Introductionmentioning
confidence: 99%